Management of The Muslim Diaspora Community In Developing The Halal Ecosystem - Finadatul Wahidah (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to analyze how diaspora Muslim communities in Taiwan such as FORMMIT manage, maintain, and develop the halal ecosystem. This study uses the perspective of collaborative governance and cultural management to understand that the management of the halal ecosystem in the Muslim diaspora community, namely FORMMIT, is not only an economic-religious activity, but also a process of strengthening identity, forming social solidarity, and producing Islamic cultural space in the context of minority communities. Data was collected through interviews with Taiwanese Muslim organization administrators, halal business actors, students, KDEI and Muslim migrant workers, and supported by field observations and documentation studies. Data analysis uses the Miles and Huberman model, namely data condensation, data presentation, and conclusion drawing by applying source triangulation to increase the validity of findings. The results of the study show that The governance of the halal ecosystem in the diaspora Muslim community in Taiwan, namely FORMMIT, shows that the community has a strategic function in ensuring halal access for minority groups by involving various parties. The Halal Ecosystem Governance carried out by FORMMIT as the Diaspora Muslim Community in Taiwan is carried out with integration between Muslim community organizations, mosques, business actors, halal certification institutions, and the KDEI government. FORMMIT as a Muslim Diaspora Organization strengthens by building collaboration and communication between community members through various forums and social activities. The results of the study show that the strengthening and sustainability of the halal ecosystem carried out by Muslim organizations in Taiwan, namely FORMMIT, is carried out through several main strategies, namely ease of access to halal information, the development of multi-stakeholder partnerships, and the promotion of halal culture to the wider community. The use of digital media is an effective means to introduce halal products and services to Muslim and non-Muslim consumers.